Gender Does Matter: Gender-Specific Outcome Analysis of 67,855 Heart Transplants - Kaczmarek, Ingo; Meiser, Bruno; Beiras-Fernandez, Andres; Guethoff, Sonja; Überfuhr, Peter; Angele, Martin; Seeland, Ute; Hagl, Christian; Reichart, Bruno; Eifert, Sandra (The Thoracic and Cardiovascular Surgeon, 2013)
Background Gender differences between donor and recipient might have an impact on the outcome after heart transplantation (HT). Data of more than 67,000 patients registered at the International Society of Heart Lung Transplantation (ISHLT) were reviewed focusing on the influence of gender differences on short- and long-term outcome after HT.Methods We performed a retrospective analysis of 67,855 cardiac allograft recipients. They received orthotopic HT between January 1, 1980 and June 30, 2009. In contrast to other studies the data for gender differences (donor gender and recipient gender) were calculated with respect to actuarial and conditional survival (without 30-day mortality).Results One-year survival was highest in male recipients of male donor hearts (mR/mD: 83.74%). The lowest 1-year outcome showed male recipients of female donor organs (mR/fD: 78.95%). Best 5-year survival rates were shown by male recipients with male donor organs (70.75%, p < 0.0001). These differences disappeared in survival conditional to 1 year, indicating that gender predominantly influences short-term outcome.Conclusions The combination male recipient/female donor carries a higher risk for early mortality, whereas female recipients/male donor reveals favorable short-term results. Gender-matched HT would be ideal, but not suitable in practice because of the shortage of organs.
Keywords: heart transplantation; survival; outcomes; gender differences